STANDARDIZATION OF HERBAL AYURVEDIC OIL FORMULATION- KSHEER BALA TAILA - Joshi, Poonam; Nanda, Deepak; Nainwal, Pankaj; Saini, Prem (Asian Journal of Pharmaceutical Research and Development, 2013)
Oils are described in Ayurveda most prominently, reason is the specificity of the oils in treatment and secondly there is a marvelous property in fats- Oil and Ghee (Indian Purified Butter), which makes these carrier of choice for different purposes. Herbal Oils work on all the three Doshas, due to the herbs processed with these oils. Ayurvedic Oils can be taken internally, because of the way these Ayurveda Oils are prepared. Ksheer Bala Taila was prepared in-house and was compared with the marketed formulation . The parameters which were determined for the evaluation are acid value, saponification value , Iodine value , Ester value, weight per ml , viscosity and refractive index. The parameters were found to be similar and hence it was suggested that these parameters could be used for standardization of ksheer Bala Taila.